Social Media Based Public Relations Management At Ma’had Aly Makkah Andong Boyolali - Dutha Bahari Esa Tyas Kurtubi Putra; Imam Makruf; Toto Suharto (International Journal of Science and Applied Science: Conference Series, 2024)
Abstract: This study aims to analyze the implementation of social media-based public relations management at Ma'had 'Ali Makkah Andong Boyolali. This research is a qualitative research. The research was conducted at Ma'had Aly Makkah Andong Boyolali. The subjects of this research were the Head of Communication Section, Ustadz Pelaksana, and Mahasantri. Data collection was conducted using interview, observation and documentation methods, then using triangulation of sources and techniques to test the validity of the data. The data obtained were analyzed using interactive model analysis, namely through data reduction, data display, and verification. The results of the study showed (1) the planning of social media-based public relations was carried out well and in accordance with the planning stages, (2) the organization of social media-based public relations went quite well, SOPs in each section had been written to facilitate HR in carrying out their duties, (3) the implementation of social media-based public relations was carried out in stages and based on Islamic principles, (4) evaluation of social media-based public relations was carried out routinely and incidentally, (5) the success factor of social media-based public relations was with the management of interesting and consistent content to always upload, while the inhibiting factor of social media-based public relations was the lack of supporting multimedia equipment.